Pengalaman Perempuan Terdiagnosis Kanker Servik: Studi Deskriptif Kualitatif - Herita, Gusti; Afiyanti, Yati; Azidin, Yustan (Akademi Kebidanan Bunga Husada Samarinda, 2024)
The diagnosis of cervical cancer triggers drastic changes in women, encompassing alterations in body image, physical issues, and biopsychospiritual impacts. Physiological challenges involve reduced appetite and stiffness, while psychological impacts include fear, feelings of disability, dependence, and role and financial stress. Spiritual disturbances can arise from the belief that this disease is a punishment from God, sometimes resulting in the loss of spiritual faith. Holistic support is necessary to help them navigate these changes. This research aims to explore the experiences of women diagnosed with cervical cancer. The study design is qualitative descriptive research, where qualitative data is obtained through in-depth interviews with 15 participants at Ulin Banjarmasin General Hospital using purposive sampling techniques. The research identifies six main themes: the initial response to the diagnosis of cervical cancer, the impact of cervical cancer on the physical aspects of daily life, the impact of the disease on psychological aspects of daily life, the impact of the disease on spiritual aspects of daily life, the adaptation of women with cervical cancer to the disease, and support from various sources. The findings conclude that women diagnosed with cervical cancer experience shock, sadness, and fear, highlighting the need for support from family, relatives, close friends, and healthcare professionals.